The science of natural disasters : when nature and humans collide - Taylor, Diane C. (Diane Carol) (Inquire and investigate., 2020)
Provides a textbook exploring the science of natural disasters, offering information on earthquakes, volcanoes, hurricanes, tornadoes, floods, and wildfires. Includes a timeline, activities and experiments, color photographs, sidebars, QR codes that link to online information, vocabulary exercises, critical thinking questions, a glossary, and further resources.